Distributional Change: Assessing the Contribution of Household Income Sources. (22nd October 2021) - Kyzyma, Iryna; Fusco, Alessio; Van Kerm, Philippe
Abstract: We develop a decomposition of changes in household income distributions by factor components to quantify the contribution of changes over time in the association between sources of income and changes in their (marginal) distributions. The two components are broken down to isolate the contribution of specific income sources. An application to the change in the distribution of household incomes in Luxembourg between 2004 and 2013 reveals contrasted results: increased association between spouse earnings, public transfers and taxes depressed the income share of poor households while changes in marginal distributions increased incomes in the upper half of the distribution.